Indonesia Economic Growth: Determinants and Prospects - Ahmad Novianto; Suharsimi Arikunto (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2021)
This research examines the impact of government expenditure and a few other factors on long-term economic growth in Indonesian provinces. This research is based on a panel data analysis of 26 provinces from 2000 to 2018. The data passed the stationarity test using Madalla and Wu's suggested Augmented Dickey Fuller (ADF) - Fisher test for panel data (1999). As a result, data at the first difference level is stagnant. The coefficient on real government expenditure is highly positive, according to this study. This indicates that government expenditure has a significant impact on Indonesia's economic growth. The impact of total government spending is examined in this study.